Linhas de errância : vidas precárias e pedagogias - Machado, Silvio Ricardo Munari (Universidade Federal de São Carlos, 2017)
Taking as a starting point the wandering lines traced around the world, we find singularities that affirm and invent other possible worlds, architecting absolutely other spaces. From these encounters, we intend to create cartographies, which allow us to think about the imbrication between these lives and pedagogies. The lives we want to find are those we call precarious lives: those that struggle for and against precarity, ontological condition and political intervention. The so-called homeless, madmen, prostitutes, old people, unemployed, drug addicts, prisoners. Young delinquents, sheltered children, beaten homossexuals, blacks-poor-peripherals in genocide, street-killers. Demonstrators, asphalt and favela, using their own bodies as targets of rubber bullets and bullets with gunpowder, brutalized by the Police State, by means of mediatic manipulation, blackblocs, midialivists, vandals, terrorists. Amarildo, Claudia, Rafael Braga Vieira. Many are the pedagogies engendered by these lives. To operate next to this population, we can find a huge network: the social service, the judiciary, health, education, philanthropy, politics, and the police. Neither of these sectors operates by itself and its operators are social workers, psychologists, lawyers, judges, guardianship counselors, police officers and pedagogues! In this research, we draw a map of the lines of pedagogy that intersect with these precarious lives and are engendered by them. We analyze the concepts of oppression and precarity. We traced the history of the concept of representation and the the lines to escape from it, affirmating difference itself. Finally, we think about the precarity of lives, pedagogues and pedagogies in the plurality and potency of “between”.
Keywords: Errância; Precariedade; Diferença; Wandering; Precarity; Difference; CIENCIAS HUMANAS::EDUCACAO